2019
DOI: 10.1039/c9ra02950h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and anticancer activity novel dimeric azatriperoxides

Abstract: An efficient method was developed for the synthesis of tetra(spirocycloalkane)-substituted a,udi (1,2,4,5,7,8-hexaoxa-10-azacycloundecan-10-yl)alkanes by a ring transformation reaction of 3,6di(spirocycloalkane)-substituted 1,2,4,5,7,8,10-heptaoxacycloundecanes with a,u-alkanediamines (1,4butane-, 1,5-pentane-, 1,7-heptane-, 1,8-octane-and 1,10-decanediamines) catalyzed by Sm(NO 3 ) 3 /g-Al 2 O 3 . Using flow cytometry, it was shown for the first time that synthesized dimeric azatriperoxides are efficient apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…We assumed that cyclic thia-diperoxides may be synthesized by a reaction of pentaoxacanes with hydrogen sulfide in a similar manner to what we reported previously for the synthesis of cyclic aza-diperoxides via the reaction of pentaoxacanes with primary amines [46,47,50]. Preliminary experiments demonstrated that 7,8,10,12,13-pentaoxaspiro [5.7]tridecane [51] (1) reacts with H2S in the presence of the catalyst Sm(NO3)3·6H2O [46][47][48][49][50] for 6 h at room temperature in tetrahydrofuran (THF) solvent to produce 7,8,12,13-tetraoxa-10-thiaspiro [5.7]tridecane (8) in 98% yield. The reaction does not proceed in the absence of a catalyst (Scheme 1).…”
Section: Chemistrymentioning
confidence: 92%
See 2 more Smart Citations
“…We assumed that cyclic thia-diperoxides may be synthesized by a reaction of pentaoxacanes with hydrogen sulfide in a similar manner to what we reported previously for the synthesis of cyclic aza-diperoxides via the reaction of pentaoxacanes with primary amines [46,47,50]. Preliminary experiments demonstrated that 7,8,10,12,13-pentaoxaspiro [5.7]tridecane [51] (1) reacts with H2S in the presence of the catalyst Sm(NO3)3·6H2O [46][47][48][49][50] for 6 h at room temperature in tetrahydrofuran (THF) solvent to produce 7,8,12,13-tetraoxa-10-thiaspiro [5.7]tridecane (8) in 98% yield. The reaction does not proceed in the absence of a catalyst (Scheme 1).…”
Section: Chemistrymentioning
confidence: 92%
“…We developed a method for the preparation of thioperoxycarbocycles through the recyclization of pentaoxacanes and heptaoxadispiroalkanes with hydrogen sulfide under the action of lanthanide catalysts. We chose lanthanide catalysts due to their high activity in recyclization reactions involving primary amines, leading to cyclic N-containing diand triperoxides [46][47][48][49][50].…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, [5][6][7][8][9][10] nitrogen-and sulfur-containing cyclic di-and triperoxides with antitumor activity have been synthesized. [5][6][7][8][9] The development of efficient methods for the preparation of new cyclic hetero-di(tri)peroxides [5][6][7][8][9][10] promotes active investigation of their transformations. It was shown that the reduction of silatriperoxycycloalkanes with PPh 3 affords siladiperoxycycloalkanes; 11 the reaction of spiro{adamantane-[2,3 0 ]-(pentaoxacane)} with o-phenylenediamine results in the synthesis of benzodioxazocine.…”
mentioning
confidence: 99%
“…5 The implemented conversion of pentaoxacane with o-phenylenediamine to benzodioxazocine 5 suggests that cyclic N-containing peroxides can be involved in reactions with binucleophilic reagents, in particular a,u-dithiols, to give new heterocycles. In contrast to the previously described methods of synthesis [5][6][7][8][9][10] and transformation of the peroxide ring, 5,11 this work for the rst time discusses the method of catalytic conversion of tetraoxazaspirotridecane to dithiazacycloalkanes.…”
mentioning
confidence: 99%